(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine how the influence of village chief’s leadership with an increase in social activities Benteng Somba Opu youth community in Barombong District. This study was quantitative with the type of survey research, the sample was 35 people. The data was analyzed statistically simple linear regression with SPSS 20 program statistics. Hypothesis testing showed that the village chief’s leadership variable was obtained (t) = 0.251 with a sig value of 0,000 because the value of the sig obtained was more than 0.05 then it showed that the value (t) obtained was significant. This meant that the village chief’s leadership variable (X) was associated with an increase in social activities of youth youth (Y), so H was accepted. Role (R Square) the influence of the village chief’s leadership on the increase in social activities of the youth of Benteng Somba Opu District of Barombong, r square value of 0.420 or 42%.